A continuous-time inequality measure applied to financial risk: The case of the European Union - Guglielmo D'Amico; Philippe Regnault; Stefania Scocchera; Loriano Storchi (International Journal of Financial Studies, 2018)
In this paper, we apply information theory measures and Markov processes in order to analyse the inequality in the distribution of the financial risk in a pool of countries. The considered financial variables are sovereign credit ratings and interest rates of sovereign government bonds of European countries. This paper extends the methodology proposed in our previous work, by allowing the possibility to consider a continuous time process for the credit rating evolution so that complete observations of rating histories and credit spreads can be considered in the analysis. Obtained results suggest that the continuous time model fits real data better than the discrete one and confirm the existence of a different risk perception among the three main rating agencies: Fitch, Moody's and Standard & Poor's. The application of the model has been performed by a software we developed, the full code is available on-line allowing the replication of all results.
Keywords: C61; G17; G32; 330; Markov chain; dynamic entropy; sovereign credit rating; credit spread